SPATIAL INTERACTION ANALYSIS BETWEEN KENDARI CITY AND SOUTH KONAWE REGENCY - irmayanti faena; Irfan Ido; Fitriani Fitriani (USN Kolaka, 2019)
This study aims to: (1) To determine the spatial interaction of the driving factors of Kendari City and South Konawe District based on the attractiveness of Kendari City as a center of higher education (2) To find out the spatial interactions and the driving factors of Kendari City and South Konawe District based on the attractiveness of Kendari City as the center of the vegetable commodity market. This research uses descriptive analysis method, Location Quotient (LQ) and Gravity analysis. The results show (1) Spatial interaction and driving factors of Kendari City and South Konawe Regency based on the attractiveness of Kendari City as a center of higher education, it can be seen that the one with a very strong interval value is Ranometo District. While the Konda District has a fairly strong interval value and 20 other Districts have a non-strong interval value. The dominant motivating factor in choosing tertiary institutions is the ease of socializing. (2). The spatial interaction between Kendari City and South Konawe Regency based on Kendari City as the center of the vegetable commodity market can be seen that West Ranometo District and Konda District have very strong interval values, while Landono District has Strong interval values. The dominant driving factor that causes farmers to sell their agricultural products in Kendari City, especially the Baruga market, is because this market has a difference with other markets in Kendari City.